Blood–Brain Barrier Disruption Is Not Associated With Disease Aggressiveness in Amyotrophic Lateral Sclerosis - Prell, Tino; Vlad, Benjamin; Gaur, Nayana; Stubendorff, Beatrice; Grosskreutz, Julian (Frontiers in Neuroscience, 2021)
The pathogenesis of the fatal neurodegenerative condition amyotrophic lateral sclerosis (ALS) remains to be fully understood. Blood–brain barrier damage (BBBD) has been implicated as an exacerbating factor in several neurodegenerative conditions, including ALS. Therefore, this cross-sectional study used the novel D50 progression model to assess the clinical relevance of BBBD within a cohort of individuals with either ALS (n = 160) or ALS mimicking conditions (n = 31). Routine laboratory parameters in cerebrospinal fluid (CSF) and blood were measured, and the ratio of CSF to serum albumin levels (Qalb) was used as a proxy measure of BBBD. In the univariate analyses, Qalb levels correlated weakly with disease aggressiveness (as indicated by individual D50 values) and physical function (as measured by ALS Functional Rating Scale). However, after adjustment for cofactors in the elastic net regularization, only having limb-onset disease was associated with BBBD. The results reported here emphasize the clinical heterogeneity of ALS and the need for additional longitudinal and multi-modal studies to fully clarify the extent and effect of BBBD in ALS.